CORRELATIONS OF MORPHO-AGRONOMIC TRAITS AND FORAGE QUALITY PROPERTIES IN DIVERSE RED CLOVER (TRIFOLIUM PRATENSE L.) COLLECTION - Branković, Gordana Radivoje; Radinović, Irena; Vasiljević, Sanja (Journal of Agricultural Sciences (Belgrade), 2022)
Red clover is important perennial forage legume and rich source of highly nutritional voluminous forage for livestock feed, which is continuously improved by plant breeding efforts which relies significantly on traits correlation studies. A two-year field trial was conducted at the site Rimski Šančevi, Novi Sad, Serbia, and a completely random block design with three replications was an experimental layout. The aim of this research was to assess correlations of important morpho-agronomic traits and forage quality properties of 46 red clover accessions of diverse origin. The highest highly significant Spearman's correlation coefficient (0.97**) was found between the branch number and internode number per stem in the first experimental year. The green mass yield and the dry matter yield in both years had highly significant very high (0.95**) and high (0.86**) correlation, respectively. The stem height and internodes number per stem had intermediate, statistically highly significant correlation in both years (0.68** and 0.50**), and stem height exhibited intermediate statistically highly significant correlation in both years with green mass yield (0.57** and 0.62**) and dry matter yield (0.60** and 0.56**). Thus, the indirect selection for higher plants with higher numbers of internodes per stem may contribute to accomplishing higher yield performance per plant. Although the branch number showed highest, positive, statistically highly significant correlation with internode number per stem, and intermediate, positive, statistically highly significant correlation with stem height, this trait had low correlation with green mass yield and dry matter yield and cannot be used as criterion for indirect selection.
Keywords: Trifolium pratense L., internode number per stem, branch number, stem height, stem thickness, middle leaflet length and width, green mass yield, dry matter yield, indirect selection, forage quality.